METHODOLOGY FOR DEFINING RISK INDICES APPLICABLE TO SUBSEA EQUIPMENT - Maturana, Marcos Coelho; Schleder, Adriana Miralles [UNESP]; Frutuoso e Melo, Paulo Fernando Ferreira; de Barros, Leonardo Oliveira; Martins, Marcelo Ramos (ASME International, 2022)
As offshore operations explore deeper and deeper reserves, there may be an increase in the number of accidents and failures, resulting in greater challenges for the sustainability of these operations. In this sense, the planning of inspections and maintenance of subsea equipment assumes a central role, both in terms of costs and in relation to the risks involved. Risk Based Inspection (RBI) appears as possibility to address these challenges, and have been more and more employed to assist the operators in finding cost-effective solutions while considering safety aspects. For the effective application of RBI tools, it is necessary to calculate the risk in order to facilitate the comparison of inspection plan alternatives, also allowing the comparison of each possible solution risk with a Risk Acceptance Criteria (RAC) accepted by society. In this sense, this paper discusses a risk calculation method that can be used in the quantitative optimization process (aimed at improving subsea equipment inspection plans), considering the inspection plan as a whole, the general characteristics of the equipment and its operation, and a RAC.
Keywords: Offshore subsea equipment; Risk Acceptance Criteria (RAC); Risk Analysis; Risk Based Inspection (RBI)